Network meta-analysis of the efficacy of endoscopic cardia peripheral tissue scar formation (ECSF) in the treatment of gastroesophageal reflux disease. - Chaoyi Shi; Shunhai Zhou; Xuanran Chen; Diyun Shen; Tianyue Wang; GeSang ZhuoMa; Mingzhi Feng; Yan Sun; Jun Zhang (PLoS ONE)
Endoscopic antireflux therapy is widely used in clinical practice. Peroral endoscopic cardial constriction (PECC), antireflux mucosal intervention (ARMI), and radiofrequency ablation (RF) possess analogous antireflux mechanisms. This comprehensive systematic review and meta-analysis aimed to evaluate and compare the safety and effectiveness of antireflux therapy during endoscopic cardia peripheral tissue scar formation (ECSF) procedures. We comprehensively searched the Web of Science, PubMed, Embase, China National Knowledge Infrastructure, and Wan-Fang databases for articles published from January 1990 to January 2024. Network meta-analysis (NMA) was used to assess the outcomes, with outcome metrics including the Gastroesophageal Reflux Questionnaire (GERD-Q) score, proton pump inhibitor discontinuation rate, pH <4.2 percent acid reflux time (AET), lower esophageal pressure (LES pressure), DeMeester score, adverse events, and patient satisfaction. Twenty studies involving 1219 patients were included. PECC was significantly superior to RF in lowering the patients' postoperative GERD-Q scores(MD = -2.34, 95% confidence interval (CI): [-3.02, -1.66]), augmentation of LES pressures(MD = 3.22, 95% CI: [1.21, 5.23]), and having a lower incidence of serious adverse events. ARMI was preferable to PECC (MD = -2.87, 95% CI [-4.23, -1.51])and RF (MD = -1.12, 95% CI [-1.79, -0.54]) in reducing the AET percentage, but was not as effective as PECC in lowering GERD-Q scores(MD = -1.50, 95% CI [-2.47, -0.53]). The incidence of adverse effects was less than 10% for all interventions, with most of them mildly self-resolving. Each ECSF procedure resulted in a favorable outcome in patients with GERD. Considering the safety and efficacy of treatment, PECC was the most favorable choice among ECSF procedures.